The effect of silver-containing sorbent on red blood cells during hemosorption: an in vitro study - L. N. Rachkovskaya; A. A. Smagin; V. V. Nimaev; A. Yu. Demura; E. E. Rachkovsky; E. S. Yastrebova; V. P. Maltsev; M. A. Korolev; A. Yu. Letyagin (Сибирский научный медицинский журнал)
The aim of the study was to investigate the influence of the original porous silver–containing sorbent on the morphofunctional parameters of red blood cells during in vitro hemoperfusion. Material and methods. Donor blood was perfused through glass columns filled with a sorbent based on porous aluminum oxide, polydimethylsiloxane and silver nanoclusters and a sorbent without silver. The effect of a silver-containing sorbent on the change in morphofunctional parameters of red blood cells after perfusion through sorbents was determined by scanning flow cytometry. Results and their discussion. Due to the uniformity of the distribution of silver (0.1 %) over the sorbent granules, the parameters of the porous structure – the specific surface area and pore volume – practically do not change compared to the sorbent without silver. Morphological parameters of original donor blood and after hemoperfusion are within the norm. The functional parameters are also normal, although the introduction of silver in to the sorbent slightly increases the number of active band 3 (B3) proteins on erythrocyte membranes, both in comparison with the donor red cell mass as a control and in comparison with the sorbent without silver. There is also an increase in the ultimate extensibility of the erythrocyte membrane compared to the original blood (2.2 times) and the sorbent without silver (1.4 times). Conclusions. A sorbent modified with silver and a sorbent without silver does not have a damaging toxic effect on the morphofunctional parameters of blood under perfusion conditions. The mechanisms affecting the indicators of the ultimate extensibility of the erythrocyte membrane after blood perfusion through a silver-containing sorbent require further research.